(untitled) (Revista Brasileira de Contabilidade e Gestão, 2020)
Faced with scenarios in Brazil and in the world, with corruption scandals in companies and public bodies, measures to detect and prevent fraud, as well as the generation of evidence for the judging bodies, became necessary. Given the relevance, this work aims to highlight and differentiate the roles of criminal accounting expertise and forensic accounting, based on bibliometric analyzes of articles published on the referred topics in the period from 1999 to 2019. For the subsidy of bibliometric research, hedid use of the Spell, Scielo and Google Scholar bases in a quali-quanti approach, in order to present data from the art of scientific production carried out in recent years on the topic, which is so relevant to justice in society. Twenty articles were found, a lower number due to the importance of the topic. It was concluded that there are few authors who delve into the theme with published works and there are similarities and differences between Criminal Expertise and Forensic Accounting, both areas aiming at conflict resolution and using science in favor of clarifying facts and from the truth, with a critical sense, a skeptical eye, in-depth knowledge of accounting, legal aspects and degrees of expertise, the main differences are in the bodies that determine the jobs, as well as the regularization and training of professionals.